2016
DOI: 10.1016/j.juro.2015.10.138
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Prolapse Recurrence after Native Tissue Anterior Vaginal Suspension Procedure with Intermediate to Long-Term Followup

Abstract: Anterior vaginal wall suspension for symptomatic stage 2 anterior prolapse offers a native tissue vaginal repair with minimal morbidity and a low anterior recurrence rate at intermediate to long-term followup. However, 33% of patients required secondary prolapse compartment procedures from 0.6 to 13 years later, highlighting the importance of long-term followup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 17 publications
0
16
0
2
Order By: Relevance
“…In our study, at six months, all patients had significantly improved anatomical results (median point C/D POPQ score 0) and no cases of recurrence were noted. Lavelle et al (24) reported their experience with POP recurrence after native tissue anterior vaginal suspension procedures. After a mean follow-up at 5.8±3.7 years, they reported prolapse recurrence rates of approximately 45% (isolated anterior 7.4%, isolated apical 10.7%, isolated posterior 8.3%, multiple compartments 19%) (24).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, at six months, all patients had significantly improved anatomical results (median point C/D POPQ score 0) and no cases of recurrence were noted. Lavelle et al (24) reported their experience with POP recurrence after native tissue anterior vaginal suspension procedures. After a mean follow-up at 5.8±3.7 years, they reported prolapse recurrence rates of approximately 45% (isolated anterior 7.4%, isolated apical 10.7%, isolated posterior 8.3%, multiple compartments 19%) (24).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with prior publications, the data set for this manuscript was reviewed retrospectively, but data in the database were prospectively maintained since 2004 and data prior to 2004 was collected retrospectively. Data extracted included patient demographics, history of prior prolapse repairs, and continence surgeries and physical exam with Baden‐Walker (BW) grading of prolapse at baseline and follow‐up.…”
Section: Methodsmentioning
confidence: 99%
“…10 Primary outcome was failure defined by either secondary compartment prolapse recurrence (BW grade of >2) on follow-up examination or re-operation for recurrent symptomatic POP, following guidelines set forth by the NICHD and outcomes used by other studies of prolapse repair in the literature. [6][7][8][9][10][11][12] Time to anatomic failure or re-operation, type of secondary compartment POP, and secondary POP surgical repairs were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Surgery may be indicated for women experiencing symptomatic prolapse who have failed or opted out of conservative therapies. There is an 11% to 19% lifetime risk for women undergoing surgery for pelvic organ prolapse, and there is a reoperation rate of up to 30% after the initial surgery …”
Section: Pelvic Organ Prolapsementioning
confidence: 99%
“…There is an 11% to 19% lifetime risk for women undergoing surgery for pelvic organ prolapse, and there is a reoperation rate of up to 30% after the initial surgery. [29][30][31]…”
Section: Pelvic Organ Prolapsementioning
confidence: 99%